2003
DOI: 10.1002/path.1418
|View full text |Cite
|
Sign up to set email alerts
|

Molecular alterations in pancreatic carcinoma: expression profiling shows that dysregulated expression of S100 genes is highly prevalent

Abstract: In order to expand our understanding of the molecular changes underlying the complex pathology of pancreatic malignancy, global gene expression profiling of pancreatic adenocarcinoma compared with normal pancreatic tissue was performed. Human cDNA arrays comprising 9932 elements were interrogated with fluorescence-labelled normal and adenocarcinoma samples (nine tumours, three normal pancreata, and three cell lines). The data were analysed for differential gene expression, which was confirmed by serial analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
110
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(122 citation statements)
references
References 21 publications
9
110
1
2
Order By: Relevance
“…We and others have recently undertaken such analyses of normal pancreas and pancreatic adenocarcinoma (Crnogorac-Jurcevic et al, 2003;Logsdon et al, 2003;Hustinx et al, 2004;Grutzmann et al, 2005) and our cDNA array data showed overexpression of spermassociated antigen 1 (SPAG1) in cancer cells (Missiaglia et al, 2004).…”
Section: Introductionmentioning
confidence: 77%
“…We and others have recently undertaken such analyses of normal pancreas and pancreatic adenocarcinoma (Crnogorac-Jurcevic et al, 2003;Logsdon et al, 2003;Hustinx et al, 2004;Grutzmann et al, 2005) and our cDNA array data showed overexpression of spermassociated antigen 1 (SPAG1) in cancer cells (Missiaglia et al, 2004).…”
Section: Introductionmentioning
confidence: 77%
“…A total of 10 individual studies on gene expression in pancreatic cancer have been published so far (Han et al, 2002;Iacobuzio-Donahue et al, 2002Crnogorac-Jurcevic et al, 2003;Friess et al, 2003;Grutzmann et al, 2003;Logsdon et al, 2003;Tan et al, 2003;Nakamura et al, 2004). But, the concordance of these studies is rather low, with 86 genes described in at least two independent studies of 548 genes published in eight of these studies.…”
Section: Discussionmentioning
confidence: 97%
“…25 Integrin a6b4 also is expressed at the invasive fronts in association with its ligands laminin-1 and laminin-5 in gastric cancers 26 where it is suggested to be involved in the invasion process. In pancreatic cancer, prior studies using gene microarray analysis and immunohistochemistry demonstrated that the b4 integrin subunit was upregulated when compared to normal pancreas and pancreatitis tissues 10,11,13 as well as associated with cases that presented with lymph node metastasis. 12 Furthermore, the potential role of the a6b4 integrin in metastasis is supported by studies in papillary thyroid carcinoma which suggested that the increased expression of the integrin b4 subunit in cancer lesions could play a role in the development of lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The quest for such markers has led to the use of high throughput technology such as genetic profiling and proteomics. Recent studies that included the use of genetic profiling and immunohistochemistry suggested that the integrin a6b4 is selectively overexpressed in pancreatic adenocarcinomas, [10][11][12][13] thus providing evidence of the potential role of this integrin in pancreatic cancer progression.…”
mentioning
confidence: 99%